2017
DOI: 10.4172/2155-9597.1000319
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Bacteria from Rivers Water in Algeria

Abstract: The aim of the current investigation was to look on the presence of the antibiotic resistance bacteria in natural environment in Algeria. From fresh water, multidrug resistant bacteria were harvested, and then investigated for their resistance profile and extend spectrum Beta lactamase and metallo Beta lactamase production. From isolate bacteria only Aeromonas hydrophila catch our attention, because of their metallo Beta lactamase production and alimentary and clinical impact. This finding confirmed our hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The Gram-positive methicillin resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) bacteria are also of great concern for public health. Both are known to have the potential to cause epidemics [74][75][76]. Although few studies have confirmed the presence of ESBL, MRSA, and VRE producers in the environment, where they can act as a reservoir of such resistance, their presence is nonetheless disturbing, as these genes can be transferred into human pathogens [77][78][79][80].…”
Section: Antibiotic Resistant Bacteria (Arb)mentioning
confidence: 99%
“…The Gram-positive methicillin resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) bacteria are also of great concern for public health. Both are known to have the potential to cause epidemics [74][75][76]. Although few studies have confirmed the presence of ESBL, MRSA, and VRE producers in the environment, where they can act as a reservoir of such resistance, their presence is nonetheless disturbing, as these genes can be transferred into human pathogens [77][78][79][80].…”
Section: Antibiotic Resistant Bacteria (Arb)mentioning
confidence: 99%
“…Up to now, demonstration for the emergence of antibiotic and/or disinfectant-resistant organisms in the general environment has been scarce, but in recent years, there has been an increasing number of studies and publications in this field. The occurrence of antibiotic-resistant organisms in various aquatic habitats has been described for almost all parts of the world [ 133 ], [ 134 ], [ 135 ], [ 136 ], [ 137 ].…”
Section: Chemical Disinfection From the Perspective Of Emerging Andmentioning
confidence: 99%
“…Our results were slightly differed from (Urku, 2021; Alzahrani et al, 2022) who found that isolates of P. putida were sensitive to Ciprofloxacin and resistant to Ampicillin. At the present, rivers are highly contaminated with antibiotic-resistant bacteria, transferred from sewage drainage, especially from hospitals, agricultural drainage, slaughterhouses, clinics, and animal husbandries (Djenadi, 2017). Recently, (Zaki et al, 2023) found antibioticresistant bacteria in the Nile River's raw and tap water in the Dakahlia Region of Egypt due to urbanization, accumulation of microbial contamination during different water transfers from source to homes, misuse and increased exposure to antibiotics in human treatment, in poultry, and livestock farms and agriculture, which may pose a serious ecological risk to the waters and public health.…”
Section: Discussionmentioning
confidence: 99%